EKSPLORASI NEMATODA ENTOMOPATOGEN PADA LAHAN TANAMAN JAGUNG, KEDELAI DAN KUBIS DI MALANG SERTA VIRULENSINYA TERHADAP Spodoptera Litura Fabricius - Liza Afifah; Bambang Tri Rahardjo; Hagus Tarno (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
ABSTRACTEntomopathogenic nematodes (EPNs) as biological agents, is consistedSteinernema and Heterorhabditis genus. Steinernema and Heterorhabditis whichbelonged to Steinernematidae and Heterorhabditidae families had closedrelationship to Xenorabdus and Photorabdus as bacterial symbionts respectively(Smart, 1995). Types of soil moisture, temperature, and a host affect thedistribution, survivability, host finding and reproduction of EPNs. To get theEPNs local isolates, exploration of isolates from local areas was needed. Thisresearch was aimed to identify genus and density of EPNs on the fields of corn,soybean and cabbage in Malang Areas and their virulence to the larvae ofSpodoptera litura. Research was conducted at laboratory of pest and disease(Nematological Unit), Plant Protection Department, Faculty of Agriculture,University of Brawijaya, from April to September 2012. EPNs were obtainedfrom corn field in Ngijo village, soybean field in Kendalpayak village, andcabbage field in Bumiaji village. EPNs were isolated from soil samples by usingTenebrio molitor larva. White trap method was used to attract EPNs from Thedead larva of T. molitor and the population of EPNs was counted. EPNs wereidentified based on the symptoms of color changes on the cuticle andmorphological characters. In addition, virulence of EPNs was also tested on the S. litura larva. The result showed that density of EPNs was highest on cabbage field (23.264 EPNs/0.25 ml). Density of EPNs on corn field was 16.976 EPNs/0.25 ml and the lowest density was on soybean field (15.664 EPNs/0.25 ml). Based on the color changes and morphological characters of EPN, on the cabbage field, EPNs were identified as Steinernema and Heterorhabditis and the others, EPNs were identified as Steinernema. Based on the virulence test of EPNs on S. litura larva, there was significant difference between EPNs isolate of corn and othersespecially for 24 hours after application.Keywords: identification, virulence, entomopathogenic nematodes (EPNs),Spodoptera litura